Lana and Lilly Wachowski - Keegan, Cáel M. (Book collections on Project MUSE., 2018)
"Lana and Lilly Wachowski are intensely political film writers, directors, and producers whose work has made an indelible impact on American popular culture. From The Matrix (1999) to Cloud Atlas (2012), they have left their mark as innovators in the industry, consistently pushing the boundaries of what is perceived as technically and topically possible in studio film. They are also the world's first major transgender film directors and arguably the most influential transgender cultural producers in human history. Their coming out makes possible a reevaluation of the Wachowskis' entire oeuvre as curating alternate approaches to gender, emobodiment, and perception, that might be retrospectively theorized as "trans." In this study, Cael Keegan will argue that the Wachowskis' work can be read as an aesthetic history of transgender political consciousness as it has evolved in popular media. He explores the significance of the Wachowskis as film and genre innovators who have permanently altered the technology and aesthetics of mainstream Hollywood cinema. Keegan sees the radical identities at play in many of their early films as emerging from a queer sensibility and a hoped-for sense of the body's plasticity. Moving chronologically through the Wachowskis' filmography, he uses the films' theorization of gender and embodied identity at the intersection of convergence, virtuality, biopolitical surveillance and capitalist realism to open these much-discussed works to new modes of analysis"--